THE SYMBOLIC IN AGAMA KETUJUH - Ricky Aptifive Manik (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
From their birth, people cannot free themselves from cultural identity with its values, norms, and rules. To exist in their social environment, they have to internalize those values and reject the opposite ones. Manifestation on how people internalize the values and reject the opposites can be found in literary works. This research is going to find out the internalization of the values in the subject’s self in Agama Ketujuh (AK). In theory of Lacanian Psychoanalysis, values, norms, and rules are named as The Symbolic. Therefore, this research aims to find The Symbolic in the prose of AK. Through Lacanian Psychoanalysis, trajectory of Lacanian Subject Formation is used as a method. This research found three of The Symbolic, namely ‘costum’, ‘Mamak (uncle)’, and ‘self-esteem’. Those things are internalized as an anchoring point in the ambiguity and obscurity as a Minangkabaunese.